On the Criticisms of and Obstacles to the Employer of Last Resort Policy Proposal. Issue 1 (2nd January 2019) - Levrero, Enrico Sergio
Abstract: Rising inequality in income and wealth distribution and a huge waste of human resources (in the form of labor unemployment and underemployment) has once again led to a focus on Keynesian policies against poverty, including that of the State acting as an Employer of Last Resort advanced by Minsky. After briefly summarizing Minsky's proposal and roughly calculating the financial resources needed to implement it in the case of Italy, the aim of this article is to discuss the obstacles that such a proposal may encounter and the possible measures to be adopted to overcome them. A conclusion will be drawn that a mix between Keynesian demand policies and the ELR system may be the best measure to guarantee full employment, provided that an institutional framework that is favorable to this objective is established.